Estudo da deformação plástica severa por junção por laminação assimétrica acumulada (JLAA) do alumínio AA1050 - Godoi, Renan Pereira de (2018)
Aluminum alloys are widely used in the automotive and aerospace industries due to some characteristics such as low density and high corrosion resistance, but their low tensile strength restricts a number of applications. The grain size is considered as a key factor that affects the mechanical behavior of metallic materials and the well-known Hall-Petch equation shows an improvement of strength through reduction in the average grain size. The process of severe plastic deformation (SPD) stands out precisely in the grain refinement, making it possible to obtain ultrafine grains, with average diameter between 100 to 1000nm. Among the SPD processes, the accumulative roll bonding (ARB) has an advantage over the others in aspects like productivity and volume of produced material. The use of ARB to improve the mechanical properties of aluminum alloys has been extensively studied, but some usual problems from conventional rolling persist, like the highly oriented texture that is inappropriate to conformability. The asymmetric rolling (AR) is able to solve this inconvenient texture, but it does not achieve the degree of strain needed to obtain a homogeneous fine-grained structure. In order to solve these problems, the accumulative asymmetric roll bonding (AARB) was proposed. This process aims to combine the good grain refinement achieved in the ARB with the modification on texture yielded by AR. In this work, AA1050 aluminum samples were submitted to 4, 6 and 10 AARB cycles at 350 and 400oC, that is in the range of hot thermomechanical processing. The samples were mechanically characterized by Vickers microhardness and tensile tests. The microstructures of the samples were characterized by optical microscopy, scanning electron microscopy (EBSD and failure analysis), and x-ray diffraction. The results of the characterizations showed a good quality of junction for all samples analyzed. The highest tensile strength values were obtained for the sample submitted to 6 cycles at 350 ° C. The improvement in strength was attributed to the grain refinement driven by dynamic recrystallization, yielding ultrafine grains in the range of 600 to 1000nm. The texture intensity was reduced and changed to shear components, at the same time the same yield and elongation was achieved in the rolling and the transverse directions, which indicates an improvement in the formability properties of the material.